PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA ( Studi di SMP Negeri Sub Rayon 05 Kota Semarang ) - 11.52.02.0154, Wigati Yanti (Jurnal Mahasiswa Pasca Sarjana, 2013)
The objective of the study was to determine the effect of organizational culture and work motivation on teacher performance mediate job satisfaction in SMP Negeri Sub Rayon 05 Kota Semarang, involving 175 teachers as respondents consisting of junior high school teachers in Sub Rayon 05 in Kota Semarang. Methods of data collection using the primary data, as many as 175 questionnaires distributed to respondents, whereas 161 were returned. The collected data were analyzed using SPSS 19. The results showed that organizational culture had a significant positive effect on job satisfaction and teacher performance, motivation had a significant positive effect on job satisfaction and teacher performance, job satisfaction had a significant positive effect on teacher performance and job satisfaction mediates the effect of organizational culture on teacher performance, but job satisfaction did not mediate the work motivation on teacher performance. Keywords: organizational culture, employee motivation, job satisfaction and teacher performance.